Does Organizational Culture Influence Motivation, Performance, Satisfaction, and Employee Commitment Organisational? - Aris Budiono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to determine the influence of organizational culture on employee motivation, performance, job satisfaction, and organizational commitment. In December 2023, we surveyed 100 respondents to perform a simple linear regression analysis, and 30 respondents were allocated to test the validity and reliability of the instrument. The results of the study stated that Organizational Culture has a positive effect on the motivation, performance, job satisfaction, and organizational commitment of employees. The practical consequences of the results of this study suggest that measures to strengthen positive organizational culture can be an effective strategy in increasing the level of motivation, performance, job satisfaction, and level of organizational commitment among the workforce.